Laparoscopic Intracorporeal Anastomosis - Goldstone, Robert N.; Popowich, Daniel A. (Clinics in Colon and Rectal Surgery, 2022)
Given the progression of laparoscopic surgery, questions continue to arise as to the ideal technique for a laparoscopic colectomy. The most debated of these questions is whether it is best to complete an intracorporeal (ICA) or extracorporeal (ECA) intestinal anastomosis. Here, we review the literature to date and report the equivalent safety and efficacy of ICA and ECA for laparoscopic right colectomy. However, these studies also indicate that when completed, ICA may prove beneficial with respect to earlier return of bowel function, less postoperative pain, shorter incision length, and reduced risk of wound infections. For this, we present the tips and tricks for completing all forms of laparoscopic ICAs during laparoscopic colectomy.
Keywords: laparoscopic colectomy; intracorporeal anastomosis; right colectomy; low anterior resection; ileocolic resection; optimal technique